1988
DOI: 10.1063/1.454282
|View full text |Cite
|
Sign up to set email alerts
|

Sound propagation in water–ethanol mixtures at low temperatures. II. Dynamical properties

Abstract: Measurements of the ultrasonic absorption coefficient over the entire concentration range of ethanol aqueous solutions in the frequency range 10–250 MHz and for a temperature interval extending from +30 to −40 °C are presented. Large peaks, which increase noticeably as temperature and frequency decrease, are observed in the attenuation vs composition plot. A detailed analysis of these results and of the velocity dispersion data shows that the frequency spectra are better accounted for by the concentration fluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…Details of these experiments are reported elsewhere [7,8,12]. We found that the x, T, and co dependence of c and a in the three investigated solutions are qualitatively similar, but rather anomalous.…”
Section: Sound Propagation Measurementssupporting
confidence: 52%
“…Details of these experiments are reported elsewhere [7,8,12]. We found that the x, T, and co dependence of c and a in the three investigated solutions are qualitatively similar, but rather anomalous.…”
Section: Sound Propagation Measurementssupporting
confidence: 52%
“…The same approach was proposed for C P (T) (26) and α P (T) (25). Calorimetry, ultrasound (US) propagation, and hypersound Brillouin scattering (BS) experiments (24) were used to isolate the anomalous component in the bulk water response functions by measuring each ideal normal contribution separately. All of the apparently diverging functions fit a power-law form (the solid red line) analogous to that of ideal mode coupling theory χ A T ðT Þ ≈ jT =T × − 1j −θ and predict T × ∼ 225 ± 2 K, a value identical to that found in the confined water transport parameters that support the existence of a dynamic crossover (9,13).…”
Section: Methodsmentioning
confidence: 99%
“…[23][24][25][26][27]. In confined water in which C P (T), ρ(T), and α P (T) have been measurable inside the no-man's land (T ≥ 180 K), there is evidence of very different behavior.…”
mentioning
confidence: 99%
See 2 more Smart Citations